Isolation of Palm Oil-Utilising, Polyhydroxyalkanoate (PHA)-Producing Bacteria by an Enrichment Technique - Alias, Z.; Tan, I.K.P. (Elsevier, 2005)
In early attempts to isolate palm oil-utilising bacteria from palm oil mill effluent (POME), diluted liquid samples of POME were spread on agar containing POME as primary nutrient. 45 purified colonies were screened for intracellular lipids by staining with Sudan Black B. of these, 10 isolates were positively stained. The latter were grown in a,nitrogen-limiting medium with palm olein (a triglyceride) or saponified palm olein (salts of fatty acids) as carbon source. None of the isolates grew in the palm olein medium but all grew well in the saponified palm olein medium. Of the latter however, only one isolate was positively stained with Nile Blue A, indicating the presence of PHA. this method did not successfully generate bacterial isolates which could metabolise palm olein 46 produce PHA. An enrichment technique was therefore developed whereby a selective medium was designed. The latter comprised minerals and palm olein (1 w/v) as sole carbon source to which POME (2.5 v/v) was added as the source of bacteria. The culture was incubated with shaking at 30 degrees C for 4 weeks: Out of seven isolates obtained from the: selective medium, two isolates, FLP1 and FLP2, could utilise palm olein for growth and production of the homopolyester, poly(3-hydroxybutyrate). FLP1 is gram-negative and is identified (BIOLOG) to have 80 similarity to Burkholderia cepacia. When grown with propionate or valerate, FLP1 produced a copolyester, poly(3-hydroxybutyrate-co-3-hydroxyvalerate). (c) 2004 Elsevier Ltd. All rights reserved.